O2 and CO2 permeability apparatus for sausage edible casing : design and performance test - La Choviya Hawa; Anang Lastriyanto; Dyah Ayu Arum Ambarwati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Edible casing which has good mechanical properties can substitute synthetic packaging to protect products from the evapouration of water, O2 and CO2 transmission, extend shelf life of product and prevent environmental pollution and it can be consumed along with product which packed in it. Therefore, it is important to evaluate permeability of edible casing in order to determine the value of water vapour transmission, O2 and CO2 gas transmission and thickness. The aims of this research were to determine the amount of water vapour transmission by following ASTM Standard E-96 and and evaluate gas permeability. The gas barrier properties of the casing films were analysed using manometric method (ASTM D 1434). The experimental design used in this research was Randomized Block Design with 2 factors; plasticiser type (glycerol, sorbitol, sucrose) and garlic concentration (2.5%, 5%, 10%) with three replicates. The properties evaluated were thickness and value of O2 and CO2 gas transmission. The results showed that type of plasticiser and concentration of garlic affect significantly on thickness, water vapour transmission, O2 and CO2 gas transmission. The interaction of two factors has also significantly affected on thickness, water vapour transmission, O2 and CO2 gas transmission. The best combination according to Zeleny method was obtained on sucrose plasticiser and garlic 5% with thickness 0.073 mm, water vapour transmission 0.56 g/m2/h, O2 gas transmission 1.6 × 10-4 cc.mm/m2.24h.kPa and CO2 gas transmission 3.4 × 10-4 cc.mm/m2.24h.kPa.